Interaction between Population and Environmental Degradation (The Pakistan Development Review, 2005)
Economic development and population growth in the poor areas of the earth is a subject of an essential concern for the environmental economists. Developing countries are facing and suffering by the serious problem of high population growth which is causing environmental degradation. A rapidly growing population exerts pressure on agricultural land and raises demand for food and shelter which encourages the conversion of forest land for agricultural and residential uses, now we know that growing population is a major cause of air, water, and solid waste pollution. The world population was 2.52 billion in the year 1950, which increased to 6.06 billion in 2000 and is likely to reach 8.3 billion by the year 2030. While the population size will remain almost stationary in the economically developed part of the world, around 1.2 billion, during the same period population is likely to grow in the less developed regions. This is likely to pose challenges for the economic growth and pressure on environmental resources in the developing countries. Furthermore, most of the population growth in the developing countries is likely to be concentrated in the urban areas. This has implication for increased demand for energy and water resources in the urban areas. This will also pose challenges for the management of increased solid waste, air and water pollution. One of the striking experiences of the developing